Global interactive media design industry’s sectoral analysis on interactive media awards (Journal of Graphic Engineering and Design, 2019)
• Interactive Media Design Industry continues to manipulate and rearrange the dynamics of entertainment, education, production and consumption and some similar topics in the general media. As an important new formation, “Interactive Media Awards” continues to give awards and helps us to make observations about the trends of the industry since 2006. This formation surveys all kinds of projects that have been made by Interactive media companies all over the world. It gives awards in two different sections and it is quite sufficient to analyze the general trends of the industry. These awards are very well recognized internationally. That is why it is possible that the research about that work line might find an important place in international academic circles. All over the world, the award winning from 2006 in the sector of Interactive Media had many contributions to the World. After analyzing all the data from award winnings in the chosen areas basically shows that Turkey has a very important part in the field. In a lot of different areas Turkey made very important accomplishments when it comes to Interactive Media. Both Design aspects and advertisement part of the field was used very efficiently. Turkey shows its improvement in the area with shown statistics and its development trend goes higher according to time. The findings of this research will possibly guide the future projects and might also add value to the education model of universities.
Keywords: Interactive; media; design; web; internet; advertisement; global; award